Solid Implants in Facial Plastic Surgery: Potential Complications and How to Prevent Them - Patel, Krishna; Brandstetter, Kathleyn (Facial Plastic Surgery, 2016)
Allogenic implants are an effective alternative to autologous grafts in the reconstruction of facial defects. These implants are used to reconstruct a variety of bony and soft-tissue defects, including the frontal and temporal regions; internal orbit; infraorbital rim; malar, paranasal, and nasal regions; mandible; and chin. In comparison to their autologous counterparts, alloplastic materials are more readily available, lack donor-site morbidity, decrease surgical time and cost, and still have relatively good postoperative tissue tolerance. However, these implants are not without their own spectrum of complications. Common solid implant materials include silicone, GoreTex (expanded polytetrafluorethylene; W. L. Gore & Associates Inc., Flagstaff, AZ), MedPor (high-density porous polyethylene; Porex Industries, Fairburn, GA), and Mersilene mesh (nonresorbable polyester fiber; Ethicon, Somerville, NJ). Each of these materials poses certain complication risks based on their surface contour (smooth vs. porous), pliability, and reactivity with surrounding tissue. In addition, certain implant locations within the head and neck are at risk for different postoperative complications. Although there are no evidence-based guidelines for implant reconstruction to help avoid common complications, there are several principles and techniques that are commonly employed by surgeons to help reduce complication rates. These include careful patient selection, proper choice of operative procedure, infection control practices (including pre/intraoperative systemic antibiotics, meticulous aseptic technique, impregnation/soaking of implant in antibiotic, irrigation of implant pocket with antibiotic, careful closure of tissue layers, and postoperative oral antibiotics), preoperative implant shaping, choice of surgical approach, and intraoperative surgical techniques. Larger, controlled trials are needed to confirm the efficacy of the aforementioned techniques in the reduction of postoperative complications.
Keywords: solid implants; facial reconstruction; silicone; MedPor; GoreTex